Initial Level of Locomotor Ability Student Class III At Harapan Jaya Beach State Elementary School 04 - fermana kautsar, angga; Gani, Ruslan Abdul; Kurniawan, Febi; Rahayu, Ega Trisna (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
locomotor movements are basically important aspects that children should be able to do and develop . The development and improvement of basic locomotor movements in schools through PJOK learning is the basis for children to participate in other physical activities . Research This aiming For know level ability beginning motion locomotive student class III at Pantai Harapan Jaya 04 Public Elementary School. Research This is study descriptive , with use method descriptive quantitative . Data collection techniques use test . Type of method used is TGMD test 2. Test results beginning motion locomotors implemented in class​ low at SD Negeri Pantai Harapan Jaya 04 shows part big ability student is in the category enough to reach percentage as much as 50% or 7 people, while category Good reached 21% or 3 people, category not enough reached 29% or 4 people, while very good category No There is .